Le travail soigné, ressort pour une nouvelle entreprise - Yves Clot (La Nouvelle Revue du Travail, 2012)
The article starts with the observation that constraints such as bad work and “impeded quality” are the main causes of fatigue and discomfort in modern organisations. Yet instead of trying to “heal workers” as the hygienist tradition suggests, what actually needs to be healed is work itself, by turning it into a vehicle for improving people’s quality of life. Indeed, it has been demonstrated in a number of situations that deteriorations in the quality of work has a direct effect on people’s well-being outside of work. Getting back to “wholesome labour” has several conditions: the encouragement of compromise and operational flexibility, including at the most strategic levels; the promotion of “conscious” professionalism; and the reorientation of the conflictuality inherent to any wage-labour nexus towards new objects such as the quality of work. The only way to achieve this is by abandoning any financialised conception of the firm.